Effect of Temperature and Substratum on the Germination of Dalbergia sissoo Roxb. Seed - Kumar, Adarsh; Bhatnagar, H. P. (Indian Forester, 1976)
Laboratory studies were conducted to determine the effect of different temperatures and substrates on the seeds of Dalbergia sissoo Roxb. These two factors significantly influence the germination behaviour of this species. Among all the treatments, the maximum and quicker germination was obtained at 30°C in 'Between paper' (BP) in nine days time for both fresh and one year old seed lots. The alternate temperatures between 20-30°C, 25-30°C and 30-40°C were also found to be equally effective for germination of seeds. Temperatures at 40°C and 35-40°C Were not favourable for germination in comparison to other temperatures. These studies have also brought out that stotage of the seeds at least upto one year does not appreciably changes the germination behaviour provided storage conditions are good.